Формування системи показників оцінки ефективності операційної діяльності підприємства - Александров, Віталій Володимирович; Курячий, Владислав Сергійович (НТУ "ХПІ", 2015)
В роботі пропонується система показників, необхідна для комплексної оцінки ефективності операційної діяльності підприємства. Спираючись на проведені дослідження визначено перелік основних показників, які за допомогою матричного аналізу надають адекватну оцінку операційної діяльності підприємства. Зроблено висновки по використанню методу оцінки та запропоновані шляхи підвищення ефективності операційної діяльності підприємства.

The question of improving the efficiency of operational activity is considered as one of the key in terms of financial and economic activity of the enterprise. The purpose of this article is a generalization of theoretical principles and practical experience of determination of the approach to the evaluation of the operating activities of the enterprise with the further development of the management actions of the enterprise, aimed at improving the efficiency of operational activities. In-process the offered system of indicators necessary for the all-round estimation of efficiency of operative activity of company. Based on the conducted researches identified a list of key indicators, using matrix analysis to provide an adequate assessment of the operating activities of the enterprise. Suggests ways of improving the efficiency of the operating activities of the enterprise. The use of such a model would allow, thanks to economic and logical techniques to determine the impact of changes in factors of the efficiency of the operating activities of the enterprise and further adjust and implement identified reserves in practical activity.
Forming of the system indexes of estimation efficiency operating activity of enterprise
Keywords: ефективність виробництва; прибуток; матричний метод; капітал; майно; efficiency of production; income; matrix method